INVESTIGATION AND PENETRATION OF DIGITAL ATTACKS ON ZIGBEE-BASED IOT SYSTEMS - Fal Sadikin; Nuruddin Wiranda (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
The market for Internet of Things (IoT) products and services has grown rapidly. It has been predicted that the deployment of these IoT applications will grow exponentially in the near future. However, the rapid growth of IoT brings new security risks and potentially opens up new types of attacks for systems and networks. This article outlines various techniques to carry out attacks on ZigBee-based IoT systems. We conducted penetration experiments on various possible attacks on Zigbee-based IoT. The purpose of this experiment’s results is for reference in developing an Intrusion Detection System (IDS) specifically for ZigBee-based IoT.